The β-hemolysin and intracellular survival of Streptococcus agalactiae in human macrophages. - Anubha Sagar (Public Library of Science (PLoS), 2013)
S. agalactiae (group B streptococci, GBS) is a major microbial pathogen in human neonates and causes invasive infections in pregnant women and immunocompromised individuals. The S. agalactiae β-hemolysin is regarded as an important virulence factor for the development of invasive disease. To examine the role of β-hemolysin in the interaction with professional phagocytes, the THP-1 monocytic cell line and human granulocytes were infected with a serotype Ia S. agalactiae wild type strain and its isogenic nonhemolytic mutant. We could show that the nonhemolytic mutants were able to survive in significantly higher numbers than the hemolytic wild type strain, in THP-1 macrophage-like cells and in assays with human granulocytes. Intracellular bacterial multiplication, however, could not be observed. The hemolytic wild type strain stimulated a significantly higher release of Tumor Necrosis Factor-α than the nonhemolytic mutant in THP-1 cells, while similar levels of the chemokine Interleukin-8 were induced. In order to investigate bacterial mediators of IL-8 release in this setting, purified cell wall preparations from both strains were tested and found to exert a potent proinflammatory stimulus on THP-1 cells. In conclusion, our results indicate that the β-hemolysin has a strong influence on the intracellular survival of S. agalactiae and that a tightly controlled regulation of β-hemolysin expression is required for the successful establishment of S. agalactiae in different host niches.